Angulated small nests and cords: Key diagnostic histopathologic features of infiltrative basal cell carcinoma can be identified using integrated reflectance confocal microscopy‐optical coherence tomography. (12th October 2020) - Gill, Melissa; Sahu, Aditi; Alessi‐Fox, Christi; Cordova, Miguel; Gonzalez, Salvador; Iftimia, Nicusor; Aleissa, Saud; Navarrete‐Dechent, Cristian; Dusza, Stephen; Rossi, Anthony; Marghoob, Ashfaq A.; Rajadhyaksha, Milind; et al.
Abstract: Background: Accurate basal cell carcinoma (BCC) subtyping is requisite for appropriate management, but non‐representative sampling occurs in 18% to 25% of biopsies. By enabling non‐invasive diagnosis and more comprehensive sampling, integrated reflectance confocal microscopy‐optical coherence tomography (RCM‐OCT) may improve the accuracy of BCC subtyping and subsequent management. We evaluated RCM‐OCT images and histopathology slides for the presence of two key features, angulation and small nests and cords, and calculated (a) sensitivity and specificity of these features, combined and individually, for identifying an infiltrative BCC subtype and (b) agreement across modalities. Methods: Thirty‐three RCM‐OCT‐imaged, histopathologically‐proven BCCs (17 superficial and/or nodular; 16 containing an infiltrative component) were evaluated. Results: The presence of angulation or small nests and cords was sufficient to identify infiltrative BCC on RCM‐OCT with 100% sensitivity and 82% specificity, similar to histopathology (100% sensitivity, 88% specificity, kappa = 0.82). When both features were present, the sensitivity for identifying infiltrative BCC was 100% using either modality and specificity was 88% on RCM‐OCT vs 94% on histopathology, indicating near‐perfect agreement between non‐invasive and invasive diagnostic modalities (kappa = 0.94). Conclusions: RCM‐OCT can non‐invasively identify key histopathologic features of infiltrative BCC offering a possible alternative to traditional invasive biopsy.